Imaging fascicular organization of rat sciatic nerves with fast neural electrical impedance tomography - Enrico Ravagli (Nature Portfolio, 2020)
To be successful, selective neuromodulation requires a non-invasive method of imaging the fascicular anatomy of peripheral nerves. Here, the authors show the applicability and reliability of fast neural electrical impedance tomography for this purpose and provide its validation against the gold standards of invasive imaging.